Providing a safety net: A qualitative study on supporting medical students during goals of care discussions - Barker, Conor; Cheng, Brooke; Chen, Marian; Hatala, Rose (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Background: Engaging in effective goals of care (GOC) discussions with patients is a critical skill for physicians. Medical students, however, often feel unprepared, unsupported and uncomfortable leading these conversations. We undertook the current study to explore senior medical students' experiences with GOC discussions during their clinical training, examining when and how (and when not and how not) GOC discussions impacted them and the influence of supervision on their GOC learning.Methods: We used qualitative interpretive description as our methodology. Fourth-year medical students at a single university were invited to voluntarily participate. Qualitative semi-structured interviews were used to foster rich discussion about students’ GOC experiences during their clinical rotations. Data collection and analysis proceeded iteratively. All investigators participated in data analysis using an inductive, constant comparison approach to identify themes and subthemes.Results: Eleven fourth-year medical students were interviewed between 2021 and 2022. As students observed and conducted GOC conversations, participating in the conversation with a supportive clinical supervisor and with patients they knew appeared to positively influence students. In less supported environments, students experienced challenges during GOC conversations, reflected through perceived limitations and feelings of uncertainty. Supervisors also played an important role in helping students navigate a range of emotional responses to these conversations.Conclusions: Rather than shielding students from difficult conversations, supervisors can positively impact students’ experiences by supporting them to engage in GOC discussions, thereby providing them with the skills to support patients through challenging moments.